2006
DOI: 10.1017/s1047951105002088
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of procalcitonin after pediatric cardiothoracic surgery

Abstract: Procalcitonin appears to be an early and sensitive marker of bacterial infection in a variety of clinical settings. The use of levels of procalcitonin to predict infection in children undergoing cardiac surgery, however, may be complicated by the systemic inflammatory response that normally accompanies cardiopulmonary bypass. The aim of our study was to estimate peri-operative concentrations of procalcitonin in non-infected children undergoing cardiac surgery. Samples of serum for assay of procalcitonin were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Post-operative increases in PCT in adults were generally small (0.5–7 ng/ml) (3) and close to suggested cut-offs for identifying bacterial infections in other settings (0.5–2 ng/ml) (1820). In contrast, Michalik et al and Hammer et al reported occasional large increases in PCT (>50 ng/ml) in pediatric patients undergoing cardiothoracic surgery with cardiopulmonary bypass (12,15). Our study identified a substantial subset of patients (13%) who developed very high PCT levels (>20 ng/ml) by 24 hours post-operation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Post-operative increases in PCT in adults were generally small (0.5–7 ng/ml) (3) and close to suggested cut-offs for identifying bacterial infections in other settings (0.5–2 ng/ml) (1820). In contrast, Michalik et al and Hammer et al reported occasional large increases in PCT (>50 ng/ml) in pediatric patients undergoing cardiothoracic surgery with cardiopulmonary bypass (12,15). Our study identified a substantial subset of patients (13%) who developed very high PCT levels (>20 ng/ml) by 24 hours post-operation.…”
Section: Discussionmentioning
confidence: 89%
“…Several prior studies of PCT and CRP after pediatric cardiothoracic surgery have included neonates and infants, but always in combination with older children (58, 11–15). Younger patients have immature immune responses and tend to have more complex surgeries, including longer bypass/aortic cross clamp times and the use of deep hypothermic circulatory arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Peak PCT values, measured by the immunoluminometric assay, range from 0.5 to 7.0 ng/ml [29,31-40,42-44,46-48]. …”
Section: Methodsmentioning
confidence: 99%
“…Few studies have described the normal post-operative procalcitonin serum-level kinetics after cardiopulmonary bypass in children. [10][11][12][13][14][15][16][17] According to these studies, the rate of procalcitonin rises to a maximum peak of 24-48 hours after the surgery and then decreases to a normal value after the third post-operative day. The purpose of this study was to evaluate the diagnostic value of procalcitonin as a marker of infection after cardiopulmonary bypass in children.…”
Section: Ardiopulmonary Bypass Is Often Used Formentioning
confidence: 99%
“…11 Threshold values that were previously identified as defining normality ranged from 1.1 to 2.2 nanograms per millilitre for the first post-operative days. [10][11][12][13][14][15] This difference is probably explained by the use of new definitions of paediatric infection, [18][19][20][21] whereas previous studies were based on older adult infection definitions (1992). 23 The distinction of several age groups with regard to clinical and constant biological values allows us more precision, whereas previous misclassification might have concerned cases of systemic inflammatory response syndrome.…”
Section: Before Pod3mentioning
confidence: 99%